2017
DOI: 10.1371/journal.pone.0166299
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training Elicits Higher Enjoyment than Moderate Intensity Continuous Exercise

Abstract: Exercise adherence is affected by factors including perceptions of enjoyment, time availability, and intrinsic motivation. Approximately 50% of individuals withdraw from an exercise program within the first 6 mo of initiation, citing lack of time as a main influence. Time efficient exercise such as high intensity interval training (HIIT) may provide an alternative to moderate intensity continuous exercise (MICT) to elicit substantial health benefits. This study examined differences in enjoyment, affect, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
152
3
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(181 citation statements)
references
References 32 publications
17
152
3
9
Order By: Relevance
“…More importantly, it has been observed that HIIT improved body composition (total or appendicular fat and lean masses), muscle function (muscle mass and power), aerobic capacities (VO 2max ) or reduced cardiometabolic risk factors (waist circumference, waist-hip circumference ratio, diastolic blood pressure and fasting glucose levels) in older adults [26][27][28][29][30][31][32][33]. Finally, HIIT elicited similar or higher enjoyment and adherence levels than moderate-intensity continuous training [34,35].…”
Section: Introductionmentioning
confidence: 98%
“…More importantly, it has been observed that HIIT improved body composition (total or appendicular fat and lean masses), muscle function (muscle mass and power), aerobic capacities (VO 2max ) or reduced cardiometabolic risk factors (waist circumference, waist-hip circumference ratio, diastolic blood pressure and fasting glucose levels) in older adults [26][27][28][29][30][31][32][33]. Finally, HIIT elicited similar or higher enjoyment and adherence levels than moderate-intensity continuous training [34,35].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, it follows that as long as HIIT/SIT protocols can limit the number and duration of high intensity efforts, affective valence may decrease to a similar or lower extent compared to MICT, and could therefore be perceived more favourably by inactive individuals. Indeed, several, although not all (Dekker & Ekkekakis, 2017), studies have reported that participants find HIIT/SIT similarly (Green et al, 2017;Jung et al, 2014;Vella, Taylor, & Drummer, 2017) or more (Malik, Williams, Bond, Weston, & Barker, 2017;Thum, Parsons, Whittle, & Astorino, 2017) enjoyable when compared with MICT.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, HIIT is noted to be more enjoyable than traditional, continuous training (Thum et al. 2017), has higher compliance in patient populations than continuous training (Shiraev and Barclay 2012), and is noted to have equal or improved clinical outcomes in a number of aging‐related cardiovascular or metabolic disorders (Ramos et al. 2015; Cassidy et al.…”
Section: Introductionmentioning
confidence: 99%